VERBAL REPRESENTATION ABILITIES AND PROCESSES IN HOTS PROBLEM SOLVING BASED ON ADVERSITY QUOTIENT - Herlina, Anita; Syaifuddin, Moh; Wurianto, Arif Budi (Universitas Labuhanbatu, 2025)
Purpose – The learning process in schools presents a variety of challenges, one of which is the impact of teaching methods, student difficulties, and external factors on the learning process. One of the main challenges is the teaching approach that still relies heavily on mechanistic methods, which often makes learning mathematics feel meaningless for students. The purpose of this study is to analyze students' verbal representation thinking ability and process in HOTS problem-solving based on the Adversity Quotient.Methodology – The research approach employs a mixed-methods design. The subjects in this study are students of Class X (Grade 10) at SMKS Muhammadiyah 5 Srono, consisting of 35 students. Data analysis techniques utilize tests, questionnaires, interviews, and observations.Findings – The study's results showed that students' verbal representation abilities and processes in HOTS problem-solving, as measured by the Adversity Quotient, were classified as good for students who achieved high scores. The higher a student's resilience at the Adversity Quotient stage in facing challenges, the better their verbal representation abilities and processes in HOTS problem-solving.Contribution – The contribution of this study is to provide an overview of how the right learning stimulus, related to students' resilience, can enhance the ability and thought process of verbal representation in HOTS problem-solving.